ثقافات لتأهيل الدعاة في الجامعة الإسلامية بالمديمنة المنورة - Ganang Prihatmoko; Anwar, Saeful; Tamam, Abas Mansur; Alim, Akhmad (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2023)
This research departs from the discovery in the field of the weaknesses of some preachers who graduated from Islamic universities in several scientific insights. The aim of the study was to explore the educational curriculum at the sharia faculty at the Islamic University of Medina which produced scholars and preachers and analyzed it with the guide book Tsaqafah Daiyah by Yusuf Qardhawi. The conclusion states that the curriculum of the Sharia faculty is dominated by material related to Islamic Tsaqafah, namely fiqh, ushul fiqh, hadith, interpretation, besides there is also material such as morals at work, Islamic values. It's just that this material is not enough to realize the goals and standards of expected graduates, so there needs to be some curriculum material that needs to be added, including subject matter related to Tsaqafah waqi'iyah and scientific Tsaqafah